Clinical and Economic Impact of Community-Onset Urinary Tract Infections Caused by ESBL-Producing Klebsiella pneumoniae Requiring Hospitalization in Spain: An Observational Cohort Study - Dawid Rozenkiewicz; Erika Esteve-Palau; Mar Arenas-Miras; Santiago Grau; Xavier Duran; Luisa Sorlí; María Milagro Montero; Juan P. Horcajada (MDPI AG, 2021)
Objective: To analyze the clinical and economic impact of community-onset urinary tract infections (UTIs) caused by extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae requiring hospitalization. Methods: A retrospective cohort study that included all adults with a UTI caused by K. pneumoniae that were admitted to a tertiary care hospital in Barcelona, Spain, between 2011 and 2015. Demographic, clinical, and economic data were analyzed. Results: One hundred and seventy-three episodes of UTIs caused by K. pneumoniae were studied; 112 were non-ESBL-producing and 61 were ESBL-producing. Multivariate analysis identified ESBL production, acute confusional state associated with UTI, shock, and the time taken to obtain adequate treatment as risk factors for clinical failure during the first seven days. An economic analysis showed differences between ESBL-producing and non-ESBL-producing K. pneumoniae for the total cost of hospitalization per episode (mean EUR 6718 vs EUR 3688, respectively). Multivariate analysis of the higher costs of UTI episodes found statistically significant differences for ESBL production and the time taken to obtain adequate treatment. Conclusion: UTIs caused by ESBL-producing K. pneumoniae requiring hospitalization and the time taken to obtain adequate antimicrobial therapy are associated with worse clinical and economic outcomes.